RISK RELATED TO INVESTING IN ENCUMBERED REAL ESTATE - Elżbieta Zagórska; Łukasz Makowski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
The aim of the paper is to underline the risks associated with investing in the so called encumbered real properties, that is the risk involved in purchase of a real property with tenants, easement of passage or transmission, a latent legal defect, being a historical property, property at a bailiff’s auction, or divested by a debtor.